Ultraviolet second harmonic generation from Mie-resonant lithium niobate nanospheres - Wang Jiayi (De Gruyter, 2021)
Lithium niobate (LN), as a nonlinear material with a large nonlinear susceptibility, has been widely employed in second harmonic generation (SHG) up to ultraviolet (UV) frequency range due to its broad low-absorption window. In nanophotonics, it is possible to harness the Mie resonances associated with the single dielectric particles to boost the nonlinear light–matter interactions. Here, we fabricate single Mie-resonant LN nanospheres on a SiO2 substrate via the femtosecond (fs) laser ablation technique. By exploiting the magnetic dipole (MD) Mie resonance, UV SHG from the LN nanosphere is significantly enhanced with a measured conversion efficiency of 4.45 × 10−8 under the excitation of an fs laser at 750 nm. The single LN nanospheres achieved in this work could serve as Mie resonators for building nonlinear nanophotonic devices such as frequency converters and quantum light sources, etc.